Assessment of Cardiovascular Disease Risk Based on Lipid Profile in Productive-Age Women - Yani, Ahmad; Patricia, Venny; Meilana, Selfa Rosi (Journal of Noncommunicable Diseases Prevention and Control, 2024)
Dyslipidemia is one of the increasing health problems in society and its prevalence continues to increase, especially due to changes in people's lifestyles. Dyslipidemia is a condition of lipid abnormalities in the blood, which is characterized by an increase in total cholesterol levels, a decrease in high-density lipoprotein (HDL) levels, an increase in low-density lipoprotein (LDL) levels, and an increase in triglyceride levels. Increased lipid profiles in Indonesia are more common in women. This incident also poses a risk of cardiovascular disease. This study aimed to describe the lipid profile in productive-age female patients and then assess the level of risk of cardiovascular disease that may occur. The research design used was a descriptive study with a cross-sectional approach. The sample in this study were all outpatients of productive-age women who underwent blood chemistry tests at Siloam Hospitals Lippo Village in 2022, which was 45 people. The results showed that abnormal lipid profiles were more common in productive women in the 25-34 year age group. Assessment of the risk level of cardiovascular disease in productive age women using the atherogenic index of plasma showed that of all respondents, there were 2 people (4.4%) with low risk, 7 people (15.6%) with moderate risk, and 36 people (80%) with high risk of experiencing cardiovascular disease.